1999
DOI: 10.1007/s004360050506
|View full text |Cite
|
Sign up to set email alerts
|

Trichinella spiralis  : proteinases in the larvae

Abstract: Under in vitro conditions, muscle larvae of Trichinella spiralis secreted minute amounts of a cysteine proteinase into the outer environment from the stichosome. The proteinase hydrolyzed azocoll at pH 5.0 but not a number of synthetic N-blocked and N-unsubstituted proteinase substrates at this pH. The reducing compound dithioerythritol enhanced the enzyme activity, but the thiol-blocking reagent sodium-p-hydroxymercuribenzoate (0.1 mM) was without effect. Phenylmethylsulfonyl fluoride (PMSF) (2 mM) and leupep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 12 publications
1
26
0
Order By: Relevance
“…They are produced by cells situated in the oesophagus or by secretive glands and are referred to as excretive-secretive products (ES). The composition of the products has been particularly well-studied in Platyhelminthes and Nematoda (Ruitenberg & Loendersloot 1971;Hinck & Ivey 1976;Matthews 1984;Knox & Kennedy 1998;Moczoń & Wranicz 1999;Jefferies et al 2001;Irwin et al 2004). The enzymes contained in ES products (phosphatases, aminopeptydases, oxidoreductases, esterases, glucosidases) are referred to as penetrating enzymes.…”
Section: G -Glossiphonia Complanatamentioning
confidence: 99%
See 1 more Smart Citation
“…They are produced by cells situated in the oesophagus or by secretive glands and are referred to as excretive-secretive products (ES). The composition of the products has been particularly well-studied in Platyhelminthes and Nematoda (Ruitenberg & Loendersloot 1971;Hinck & Ivey 1976;Matthews 1984;Knox & Kennedy 1998;Moczoń & Wranicz 1999;Jefferies et al 2001;Irwin et al 2004). The enzymes contained in ES products (phosphatases, aminopeptydases, oxidoreductases, esterases, glucosidases) are referred to as penetrating enzymes.…”
Section: G -Glossiphonia Complanatamentioning
confidence: 99%
“…The absence of endoprotease activity, observed by Jennings & van der Lande (1967), Fischer (1970) or van der Lande (1972), may have been caused by the use of short-chain synthetic substrates for the analyses. Proteases of invertebrates are better at digesting natural substrates (haemoglobin, gelatine) with long polypeptide chains than synthetic peptides (Moczoń & Wranicz 1999).…”
Section: G -Glossiphonia Complanatamentioning
confidence: 99%
“…Immune-localization analysis also indicated that the protease was located on the inner layer of the cuticle and esophagus of the parasite, thereby suggesting a potential role in its molting and/or digestive functions [31]. The protease of Trichinella was well characterized by Moczon and Wranicz [32]. Under in vitro conditions, the muscle larvae of T. spiralis secreted minute amounts of a cysteine proteinase into the outer environment from the stichosome.…”
Section: Discussionmentioning
confidence: 90%
“…The relevant literature contains very few publications on the chemical composition and function of these products. Most papers focus on proteases contained in ES products and in fluids extracted from homogenates of internal parasites (Hinck and Ivey 1976, Matthews 1982, 1984, Knox and Kennedy 1988, McKerrow 1989, Morris and Sakanari 1994, Perteguer et al 1996, Moczoƒ and Wranicz 1999, Young et al 1999, Moczoƒ 1999, Kotomski and W´drychowicz 2001, Kinsella et al 2002, Sajid and McKerrow 2002 and those of external parasites such as ticks and follicle mites (Buczek and Madoƒ 1998, Nisbet and Billingsley 1999, Kenyon and Knox 2002. According to the authors referred to, the proteases may serve multiple functions: they may inhibit the host's blood clotting, protect the parasite from the host's immune response, facilitate parasite's migration within a tissue by decomposing the tissue barrier, enhance the hatching and moulting of larvae, and play an important role in their feeding.…”
Section: Introductionmentioning
confidence: 99%